THE RECONSTRUCTION OF FUNCTIONS USING DIDACTIC TRANSPOSITION: A FOCUS ON THE TEXTBOOKS FOLLOWING THE MALAYSIAN AND INDONESIAN MATHEMATICS CURRICULA - Nadya Syifa Utami; Sufyani Prabawanto; Phoong Seuk Yen; Arrold Rynix Anak Rambee (Malaysian journal of learning & instruction, 2025)
Purpose – This study is aimed at exploring how the topic of functions was organised into knowledge to be delivered in textbooks based on the Malaysian and Indonesian mathematics curriculum, and how the topic reconstruction in both countries differed. Methodology – A documentary research method was used in this study. Study data were collected through the examination of school mathematics textbooks, specifically Grade 8 textbooks in Malaysia and in Indonesia. The data used was the sequence of tasks presented in the chapter on functions in each country’s mathematics textbooks. This study analysed data by identifying the learning objectives of functions in both countries' curricula; categorizing task sequences in textbooks using the didactic co-determinacy framework—from domain level to sector level, theme level, and task level; and examining the similarities and differences on the topic of functions and the categorized task sequences in textbooks following the Malaysian and Indonesian mathematics curricula respectively. Findings – The findings indicated that the presentation of functions in Malaysian and Indonesian textbooks followed a similar sequence, beginning with an introduction to functions, progressing to their representation, and concluding with their application in solving real-world problems. Malaysian and Indonesian textbooks both introduced functions as a subset of relations and demonstrate various representations, including arrow diagrams, ordered pairs, tables, formulas, and graphs. While both curricula shared a common foundation in the set-theoretical definition of functions, they differed in their approach to problem-solving. Malaysian textbooks emphasized the use of function graphs more extensively, whereas Indonesian textbooks frequently utilized function formulas as problem-solving tools. Significance – This comparative study provides a practical application of the didactic transposition process of knowledge organised in the mathematics curriculum of two different countries. The results also contribute to the potential pathway for learning functions by drawing lessons from two different systems of education.